THE AFFECT OF LEARNING METHOD TOWARD ENGLISH LEARNING ACHIEVEMENT - Nur Hasan (LP2M Universitas Ibrahimy, 2012)
The aim of this research is to explore the affect of creative productiveÂ learning method and conventional learning method to increase english learning achievement through controlling self efficacy.83 students were participated on this research and divided into two groups. The first group from class VIIIB consisted ofÂ 42 students for creative productive method and the last group from class VIIIA consisted of 41 students for conventional method. The data were collected with the self-efficacy scale and english learning achievement test.The analysis being used on this research is covarian analysis. The result of this research are: there is differentiation of english learning achievement between students in the class that used creative productive method and students in the class that used conventional method. It is clarify with the F=41,111 (p< 0,01). Hence, creative procuctive method is more affected to increase english learning achievement than the conventioanl method